The Dangers of Technological Spirit - XII, Pius (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1954)
SummaryTechnology has brought man's domination of the material world to a pitch of perfection never known before. Nevertheless ,it can hardly be denied that it is, through certain circumstances, changed into a grave spiritual danger. The "Technological spirit" is a threat not only to the true concept of relations between man and God, but also to the relations among men. Wherever technology reigns supreme, there human society will be transformed into a colorless mass, into something impersonal and without substance, and this contrary to clear designs of nature and of the Creator.This so important subject has been exposed by His Holiness Pope Pius XII in his Christmas broadcast to the whole world. Here is the official translation of the major partof this speech.